'We're going to do CPR': A linguistic study of the words used to initiate dispatcher-assisted CPR and their association with caller agreement. (December 2018) - Riou, Marine; Ball, Stephen; Whiteside, Austin; Bray, Janet; Perkins, Gavin D.; Smith, Karen; O'Halloran, Kay L.; Fatovich, Daniel M.; Inoue, Madoka; Bailey, Paul; Cameron, Peter; Brink, Deon; et al.
Abstract: Background: In emergency ambulance calls for out-of-hospital cardiac arrest (OHCA), dispatcher-assisted cardiopulmonary resuscitation (CPR) plays a crucial role in patient survival. We examined whether the language used by dispatchers to initiate CPR had an impact on callers' agreement to perform CPR. Methods: We analysed 424 emergency calls relating to cases of paramedic-confirmed OHCA where OHCA was recognised by the dispatcher, the caller was with the patient, and resuscitation was attempted by paramedics. We investigated the linguistic choices used by dispatchers to initiate CPR, and the impact of those choices on caller agreement to perform CPR. Results: Overall, CPR occurred in 85% of calls. Caller agreement was low (43%) when dispatchers used terms of willingness (" do you want to do CPR? "). Caller agreement was high (97% and 84% respectively) when dispatchers talked about CPR in terms of futurity (" we are going to do CPR" ) or obligation (" we need to do CPR "). In 38% (25/66) of calls where the caller initially declined CPR, the dispatcher eventually secured their agreement by making several attempts at initiating CPR. Conclusion: There is potential for increased agreement to perform CPR if dispatchers are trained to initiate CPR with words of futurity and/or obligation.